THE EFFECT OF CUSTOMER EXPERIENCE AND BRAND TRUST ON CUSTOMER LOYALTY ON ALLBAIK CHICKEN - Hendri Antara; Siswanto Siswanto; Eska Prima Monique Damarsiwi (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
The purpose of this study was to determine the effect of customer experience and brand trust on customer loyalty at Allbaik Chicken Sawah Lebar, Bengkulu City. The sample in this study were 50 customers who made purchases at Allbaik Chicken Sawah Lebar Kota Bengkulu. Data collection using a questionnaire and the method of analysis used is multiple linear regression, test of determination and hypothesis testing.The sample in this study were 50 customers who made purchases at Allbaik Chicken Sawah Lebar Kota Bengkulu. Data collection using a questionnaire and the method of analysis used is multiple linear regression, test of determination and hypothesis testingThe sample in this study was 50 customers who made purchases at Allbaik Chicken Sawah Lebar Kota Bengkulu. Data collection using a questionnaire and the analysis method used is multiple linear regression, the test of determination, and hypothesis testing.The results of the t-test regression analysis of the customer experience brand trust variable have a partially significant effect on the customer loyalty variable of consumers at Allbaik Chicken Sawah Lebar, Bengkulu. The results of the F test at the 0.05 significance level explain that the variables of customer experience and brand trust have a significant simultaneous influence on consumer customer loyalty at Allbaik Chicken Sawah Lebar Kota Bengkulu.